Natural Products: Biochemical-Chemical Characterization, and Evidence for Therapeutic Potential - Basil D Roufogalis; Srinivas Nammi; Emanuel E Strehler (Frontiers Media S.A., 2015)
This Special Issue follows from a previous Issue entitled "Mechanism-Based Development of Natural Products for Human Health" arising from an inaugural conference on Natural Products Development held at Whistler Mountain, Canada from September 21-22, 2012. The timeliness of this issue reflects the continued growth in Natural Product research and the success of the First Issue, as judged from feedback we received and citations received. We were also encouraged by the interest in natural products research in recent years, as exemplified by the recent publication on Traditional Medicine in the prestigious journal Science (1, 2).